Father Brown. Season two [videorecording (DVD)]. - Williams, Mark, 1959-; Cusack, Sorcha, 1949-; Carroll, Nancy, 1974- (BBC, 2015)
The stakes are higher for Father Brown, who's joined once again by his secretary Mrs. McCarthy, socialite Lady Felicia Montague and her chauffeur Sid Carter who together must embark on another series of adventures to save the souls of the sleepy village of Kembleford. This season, Father Brown will face more sinister cases than ever before which will include exorcism, abduction, poison, and murder.